A five-level inverter based on differential structure - Zhang, Shaoru (2023)
Due to the advantages of low harmonic, low pollution to the power grid, and easy filtering, multilevel inverters have attracted more attention in recent years. In this paper, a five-level inverter based on the differential structure is proposed. It doesn’t need an additional bridge arm to change the polarity of the output voltage, but synthesize the structure of generating multiple voltages and changing the polarity of the output voltage. In addition, the special symmetrical structure of the inverter solves the problem of unbalanced capacitor voltage. The proposed five-level inverter is simulated by MATLAB/Simulink and the prototype is made to experiment.